Предмет: Алгебра, автор: LMFAO

Доказать тождество:
sin^3t(1+ctgt)+cos^3t(1+tgt)=sint+cost

Ответы

Автор ответа: Nik133
0
sin^3t(1+ctgt)+cos^3t(1+tgt)=sint+cost \ \ sin^3t(1+ctgt)+cos^3t(1+tgt)=sin^3t(1+frac{cost}{sint})+cos^3t(1+frac{sint}{cost})= \ \ =sin^3t+sin^3t*frac{cost}{sint}+cos^3t+cos^3t*frac{sint}{cost}=sin^3t+sin^2tcost+cos^3t+cos^2tsint= \ \ =(sin^3t+cos^3t)+sintcost(sint+cost)=(sint+cost)(sin^2t-sintcost+ \ \ +cos^2t)+sintcost(sint+cost)=(sint+cost)(sin^2t-sintcost+cos^2t+ \ \ +sintcost)=(sint+cost)(sin^2t+cos^2t)=(sint+cost)*1=sint+cost
Похожие вопросы